Binding and connecting Landeskunde. An analysis of the Dutch GFL course book Neue Kontakte - Tammenga-Helmantel, Marjon (Glottodidactica, 2019)
This study investigates the position, content and pedagogy of Landeskunde in proficiency skills-focussed Dutch foreign language teaching. It analyses the course book used most frequently in Dutch secondary education for German as a foreign language: Neue Kontakte. This research examines the position of cultural content in course materials and in explicitly formulated learning goals. Moreover, it is investigated what cultural content is introduced and whether this is either integrated in language proficiency training and connected to the world of the learners. The results show that Neue Kontakte offers a broad range of cultural topics which are either linked to the Netherlands or Dutch or to the learners’ personal environment. Additionally, Landeskunde is integrated in language proficiency exercises. On the other hand, its status is considered weak; no cultural learning goals are formulated and hardly any repetition of cultural content and little critical reflection on the foreign and the own culture are observed.